Theoreticalanalysis of self-regulation on efl learners' motivation for speaking based on transformative approach - Ahmadpour, Sahar; Asadollahfam, Hassan; Kuhi, Davud (Universidade Estadual Paulista, 2021)
This study investigated the impact of transformative instructional approach in speaking on EFL learners' motivations to speak. To this end, a total of 62 English as a foreign language (EFL) male and female learner in a language institute in Iran participated in the study. The study took over a period of two months in a classroom setting.  Participants were exposed to transformative instructional approach and their motivation was investigate following the relevant practices.  This study adopted a mixed-methods approach to data collection as well as data analysis which offers a richer and deeper insight into the findings. To measure learners’ speaking development before and after the treatment, the Preliminary English Test was implemented. The findings verified the value of transformative teaching approach in enhancing the speaking skill. Also, the findings of this study suggest that instructional conditions particularly the transformative approach enhance learners’ self-regulated behaviors when learners take on the main responsibilit'y for their learning.